HUBUNGAN ANTARA STATUS PEKERJAAN DENGAN KEMAMPUAN IBU DALAM MENSTIMULASI PERKEMBANGAN PSIKOSOSIAL OTONOMI PADA TODDLER - Widiani, Esti (LP3M STIKES MUHAMMADIYAH GOMBONG, 2018)
Toddlers are the second stage of psychosocial development after the baby is in the age range of 18 months to 36 months. Failure to skip psychosocial autonomy versus hesitation or shame can be prevented by providing good stimulation. The purpose of this study was to determine the relationship of work with the ability of the mother to stimulate psychosocial development of autonomy in infants. This study used an observational design using cross sectional. The research was conducted in Kemantren Village, Jabung District, Malang Regency. The technique used to take samples in this study was accidental sampling with a total sample of 168 respondents. The instrument used to measure the ability of the mother is a modification of the Care of Babies. HOME Inventory. The data analysis used was chi-square with no statistical results that correlated the employment status with the ability of the mother to stimulate psychosocial development of autonomy in infants with a value of p = 0.106 (p> 0.005). The recommended BKB (Toddler Family Development) group needs to be held in each Posyandu as a service center and learning center for mothers about early detection and stimulation of development